Pengaruh Keahlian Dan Independensi Auditor Terhadap Opini Audit (Studi Kasus Kantor Akuntan Publik Di Kota Makassar) - Dewi Rezki Setiawan; Tenriwaru; Muh. Arsyad (Jurnal Unicorn ADPERTISI, 2022)
This study aims to determine whether there is an influence of Expertise, and Auditor’s Independence on Audit Opinion at the Public Accounting Firm in Makassar City. The research method used in this research is quantitative method, with a saturated sampling technique (census). The method of analysis used is double linear regression. The data analysis method used was validity test, reliability test, normality test, heteroscedasticity test, multiple linear regression test, determination coefficient test, f-test and t-test. The results of the hypothesis indicate that Expertise has a positive and significant effect on Audit Opinion, and Auditor’s Independence has a positive and significant effect on Audit Opinion.